Masaier på vej. Oprindelinge folk med moderne problem - Schmidt, Robin; Vest, Morten (Denmark : Robin Schmidt for Filmselskabet Aps, 2010)
What does it mean to be a traditional Masai in 2010? The Danish crew followed three members of a Northern Tanzanian Masai nomadic community over the course of one year.
The Ngorongoro district, home to the Masai people, is one of the world's most popular safari destinations. The Masai in this region maintained their traditional way of life for centuries despite the ever growing tourism business. Living in their traditional way and far away from big cities doesn’t mean they are isolated: they are fully aware of both global warming and the financial crisis. And they are very much influenced by both.
Right to their own land is a fundamental issue: the Masai struggle with the authorities and with their own leaders, too.
Keywords: Documentary films